Stability and Antibacterial Property of Polyherbal Mouthwash Formulated Using Local Ingredients - Juman Nafea; Mohamed Edbeib; Kin Israel R. Notarte; Fahrul Huyop; Harisun Yaakub (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
The oral cavity is a home to more than 500 bacterial species. Although some of the oral bacteria are harmless, there are certain species that may cause oral plaques, bad breath, and mouth disease. Thus, maintaining a good oral hygiene is essential for a healthy mouth and body. The present study aimed to formulate a polyherbal mouthwash that may have antibacterial properties. Mouthwash formulations were prepared containing varying percentages of herbal extracts, with each formulation stored at 12 °C and 25 °C. Over the course of 12 weeks, the appearance and pH of the formulated mouthwash were measured. The mouthwash formulations maintained good homogeneity and color when stored at 25 °C, displaying lower pH level ranging between 3.71 and 4.85. Although the mouthwash stored at 12 °C maintained good homogeneity, a change in color in the formulation was evident and a more unstable pH readings were recorded. Antibacterial assay showed that mouthwash formulations stored at 25 °C had better inhibitory activity compared to those stored at 12 °C. Furthermore, mouthwash formulation containing (30% v/v) aleppo oak extract as the major ingredient conferred the greatest inhibition zone diameter (IZD = 10-18 mm) against salivary bacteria compared to formulations with (30% v/v) clove and (30% v/v) turmeric extracts as major ingredients. The best polyherbal mouthwash formulation in terms of inhibiting bacterial growth followed the 3:1:2 ratio for aleppo oak extract, clove extract, and turmeric, respectively. Therefore, the polyherbal mouthwash formulated in this study has the potential to be optimized and commercialized to antagonize growth of pathogenic oral bacteria.